2008
DOI: 10.1111/j.1469-8749.2008.03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal maturation in children with cerebral palsy and its relationship with motor functioning

Abstract: The objective of this study was to describe skeletal maturation in relation to chronological age in children with cerebral palsy (CP) aged 9 to 16 years, and to analyze the relationship between skeletal maturation and motor functioning. The skeletal age of 100 children with CP (37 females, 63 males; age 9, 11, or 13y; 73 ambulant, 27 non‐ambulant) was determined over a period of 3 years based on X‐rays of the hand (Greulich and Pyle technique). Motor functioning was measured with the Gross Motor Function Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Firstly, CP is more common among males than females . Additionally, the skeletal age of females with CP has been shown to be significantly higher than their chronological age, while this is not the case for males …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, CP is more common among males than females . Additionally, the skeletal age of females with CP has been shown to be significantly higher than their chronological age, while this is not the case for males …”
Section: Discussionmentioning
confidence: 99%
“…females with CP has been shown to be significantly higher than their chronological age, while this is not the case for males. 25 Previous studies have highlighted that males are more likely to have surgery at a younger age because of the development of lower limb deformities that do not respond to neurosurgical treatment. 26 Zwick et al 22 reported that throughout the 10-year follow-up females maintained a significantly better GGI than preoperatively, while by 7 to 8 years postoperatively males had returned to values comparable to preoperatively.…”
Section: Linear Mixed Modelmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to estimate the degree of skeletal maturity of patients with cerebral palsy using Baccetti's method and to compare it with an age-and sex-matched control group. In several articles and case reports, authors used a hand-wrist radiograph of patients with cerebral palsy to estimate skeletal maturity according to the Greulich and Pyle atlas [5,6,[38][39][40]. Compared with chronological age, both delayed and advanced skeletal age has been reported in patients with cerebral palsy [5,6,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In several articles and case reports, authors used a hand-wrist radiograph of patients with cerebral palsy to estimate skeletal maturity according to the Greulich and Pyle atlas [5,6,[38][39][40]. Compared with chronological age, both delayed and advanced skeletal age has been reported in patients with cerebral palsy [5,6,[38][39][40]. In this study, we found no difference between patients with cerebral palsy and controls in the same chronological age group, and when stratified according to sex, in the frequency of cervical vertebrae maturity stadium determined according to Baccetti's method.…”
Section: Discussionmentioning
confidence: 99%